2011
DOI: 10.1680/macr.2011.63.8.583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of w/c ratio on air-void system of foamed concrete and their influence on mechanical properties

Abstract: A study was undertaken to investigate the effect of water to cementitious material (w/c) ratio (ranging from 0 . 22 to 0 . 60) on the air-void system (air content ranging from about 10 to 70%) of foamed concrete, and their effects on the mechanical properties of foamed concrete without sand. The cementitious material used in this study was blended cement with 50% ordinary Portland cement (OPC) and 50% ground granulated blastfurnace slag (ggbs) by weight.The linear traverse method was used to characterise the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 10 publications
(8 reference statements)
1
16
0
Order By: Relevance
“…The strength of cement mortar or paste is more heavily influenced by the volume and number of large size pores and mean pore diameter than by smaller pores (Robler, Odler 1885;Kearsley, Wainwright 2002). The research (Wee et al 2011) results proved that the compressive strength of foamed concrete seems to be influenced by the spacing factor, w/c ratio and air content in relation to density. The results also indicated that the inclusion of air-voids in foamed concrete had a greater effect on compressive strength than the modulus of elasticity and it increases with increase of w/c ratio.…”
Section: Introductionmentioning
confidence: 87%
“…The strength of cement mortar or paste is more heavily influenced by the volume and number of large size pores and mean pore diameter than by smaller pores (Robler, Odler 1885;Kearsley, Wainwright 2002). The research (Wee et al 2011) results proved that the compressive strength of foamed concrete seems to be influenced by the spacing factor, w/c ratio and air content in relation to density. The results also indicated that the inclusion of air-voids in foamed concrete had a greater effect on compressive strength than the modulus of elasticity and it increases with increase of w/c ratio.…”
Section: Introductionmentioning
confidence: 87%
“…A slump of 80-100 mm was achieved with a superplasticiser (UNF-5) dosage of 0·5% by mass of cement. Specimens were cast in plastic beam moulds of dimensions 100 mm  100 mm  400 mm and were cured for 28 d. Previous concretes studied (Li et al, 2015;Liu et al, 2015b;Wee et al, 2011) were tested in accordance with ASTM C231 (ASTM, 2004) for fresh air content and ASTM C457 (ASTM, 2012) for air-void system parameters. In this work, the samples were cut into 10 mm wide slices and polished with successively finer abrasives until they were suitable for testing in accordance with ASTM C457 (ASTM, 2012).…”
Section: Foam Index Testmentioning
confidence: 99%
“…Yang and Lee studied the effect of the w/b on the performance of foam concrete. As the w/b increases, the number of fine pores decreases, and the number of large pores increases, which results in the high porosity of the foamed concrete, resulting in a low strength [12][13]. According to the research, foam concrete has excellent thermal insulation performance.…”
Section: Introductionmentioning
confidence: 97%